Pengembangan E-modul Geografi berbasis Spatial Thinking - Rahmawati Sri Pujiantiningtyas; I Nyoman Sudana Degeng; Agus Wedi (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2022)
Development of E-Module Geography based on Spatial Thinking For Senior High School Students of XI grade is purposed to produce spatial thinking e-module with good validity. The research uses research and development oriented by multimedia product, e-module. This research uses the Lee & Owen model which has five steps: analysis, design, development, implementation, and evaluation. Validation results got very good condition with an average score of 90,78 percent. Materials aspects were 82,4 percent, Media aspects were 92 percent and Educational Design aspect was 98,2 percent. Based on users’ response gave an average score of 89,3 percent and Geographic teachers gave a score of 90 percent, its mean the module had very good criteria to use as a companion book for student.